A rapid assessment technique for coastal plastic debris sampling: Applications for remote regions and community science. (May 2022) - Baak, Julia E.; Brown, Zoe O.; Provencher, Jennifer F.; Mallory, Mark L.
Abstract: Marine debris is an environmental issue of increasing importance worldwide, with 80% of marine plastics estimated to originate from land-based sources. While much work has been conducted to quantify plastics in coastal environments, many of these approaches are site-specific and not amenable to rapid surveys. We surveyed beaches around Nova Scotia, Canada for plastic and other anthropogenic debris to: 1) quantify debris density on the high tide line; and 2) test a rapid survey technique using digital photos, with applications for community science and remote regions. Most (72%) beaches in Nova Scotia contained debris, but plastic densities along the daily high tide line were relatively low (mean 0.2 debris/m 2 ) with little interannual variation. Despite small differences in plastic densities between observers, this rapid assessment technique appears viable for relative quantification and monitoring of plastic debris on beaches across large geographic scales to assess trends and sources. Graphical abstract: Unlabelled Image Highlights: We surveyed plastic debris on 46 beaches across Nova Scotia, Canada. 72% of beaches contained debris, with a mean debris density of 0.2 debris/m 2 . Debris density was higher at the storm high tide line than the daily high tide line. Debris density differed between observers and between digital and in-person counts. This rapid survey technique has applications for remote regions and community science.